2009
DOI: 10.2478/s11532-008-0089-1
|View full text |Cite
|
Sign up to set email alerts
|

Study by grazing incident diffraction and surface spectroscopy of amalgams from ancient mirrors

Abstract: Characterization of four amalgam surfaces, with different alteration degrees from Andalusia historical mirrors, has been carried out by grazing-incidence X-ray diffraction (GIXRD), and other spectroscopic techniques (SEM/EDX, XPS, and REELS). The combination of all these techniques allows determining the corrosion state of the amalgams. The results show that the amalgams are composed in all cases of a binary alloy of tin and mercury. As mercury has high vapour pressure at RT, it slowly segregates and eventuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
1
12
1
Order By: Relevance
“…SEM pictures in Fig. 4a, b showed that they are formed by the two phases of the tin amalgam, in contrast with previous studies, where the drops were characterized as rich in mercury [11] or described as formed almost entirely by mercury [4][5][6][7]. In summary, the darker and lighter zones in Figs.…”
Section: Sem-eds Investigationcontrasting
confidence: 83%
See 3 more Smart Citations
“…SEM pictures in Fig. 4a, b showed that they are formed by the two phases of the tin amalgam, in contrast with previous studies, where the drops were characterized as rich in mercury [11] or described as formed almost entirely by mercury [4][5][6][7]. In summary, the darker and lighter zones in Figs.…”
Section: Sem-eds Investigationcontrasting
confidence: 83%
“…5). Drops are present also on the top of some well pronounced craters, as previously detected [4][5][6][7][10][11][12]. SEM pictures in Fig.…”
Section: Sem-eds Investigationsupporting
confidence: 78%
See 2 more Smart Citations
“…This technique, which is usually performed on powders, is a micro-destructive technique because a small amount of the artwork is collected before performing the experiments. Non-destructive X-Ray diffraction (XRD) equipment was developed to study planar samples using techniques such as grazing incidence X-ray diffraction, which provides very precise information about the surface, atomic interface arrangement in the crystalline structure and composition of the depth profiles [16][17][18]. In addition, a recent study used Goebel crystal facilities to examine non-planar samples [19].…”
Section: Introductionmentioning
confidence: 99%